A Study of the Effectiveness of Online Marketing to Enhance Product Awareness (From the Perspective of Integrated Marketing Communication) - Limbu, Jeevan; Shrestha, Sujan Raja (Nepalese Journal of Management Science and Research, 2025)
The business environment is frequently revolving and changing, so is the tools employed in decision making process. With the growth in the internet users and application since the last three decades, organization have started shifting focus from offline marketing to online in reaching out to more customers. Online marketing is therefore not seen by many scholars as another form of promotional tools like advertising, personal selling, direct marketing among others but seen as a powerful medium of implementing the various marketing tools online to reach more targeted local and global audience. This research work investigated the effectiveness of online marketing to enhance product awareness (from the perspective of integrated marketing communication). Specifically, the work aimed at assessing the extent online platform improves product awareness through integrated marketing communication strategy. To achieve the objectives of the study, the researcher employed descriptive survey where the all-online consumers were sampled to collect relevant information regarding the effectiveness of online marketing for enhancing product awareness through integrated marketing communication. The data was analyzed using Descriptive and Inferential analysis, correlation and regression analysis.